2021
DOI: 10.21203/rs.3.rs-250806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matched comparison of corneal higher order aberrations induced by SMILE to femtosecond assisted LASIK and to PRK in correcting moderate and high myopia: 3.00mm vs. 6.00mm

Abstract: Background The refractive surgeries induce corneal higher order aberrations (C-HOAs). In this study, change of C-HOAs after small-incision lenticule extraction (SMILE) compared to femtosecond assisted laser in situ keratomileusis (femto-LASIK), and to photorefractive keratectomy with mitomycin-C (PRK) under photopic and mesopic conditions. Methods In this prospective study, age, gender, and apical corneal thickness (ACT) matched cases with moderate myopia [spherical equivalent (SE) 3.00 to 6.00D) to high myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…HOAs, except trefoil, showed a non-signi cant increase in the current study. HOA changes had a similar trend to normal corneas undergoing SMILE (9). Two points should be kept in mind.…”
Section: Aberrationsmentioning
confidence: 64%
See 1 more Smart Citation
“…HOAs, except trefoil, showed a non-signi cant increase in the current study. HOA changes had a similar trend to normal corneas undergoing SMILE (9). Two points should be kept in mind.…”
Section: Aberrationsmentioning
confidence: 64%
“…Since the epithelium remains intact in this method and a lenticule is extracted from the stroma without ap removal, it is preferred to PRK and LASIK in eyes with no history of ocular surgery. The safety and e cacy of this procedure have been con rmed as well (8,9). To the best of our knowledge, only one study reported the 6-month results of this procedure in post-PK patients (10).…”
Section: Small Incision Lenticule Extraction (Smile) Is a New Refractive Surgery Technique For Correction Of Myopiamentioning
confidence: 79%